Analisis Rasio Keuangan Terhadap Financial Distress (Pada Perusahaan Perbankan Yang Listing Di BEI Periode Tahun 2014-2016) - Nilna Izza Amalia; Ronny Malavia Mardani (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThis research aims to determine the influence of financial ratios to financial distress on banking companies listing on the BEI period 2014-2016. As for variable used in this research that is variable CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), ROA (Return On Asset), ROE (Return On Equity), LDR (Loan to Deposit Ratio) and BOPO (Operating Expenses to Operating Income. In this research using logistic regression test with the result variable CAR, ROE and LDR have a negative influence on financial distress, while the variables NPL, ROA, and BOPO have a positive influence. In this test are obtained value of chi-square of 9,807 with a significant level of 0,279.Keywords: Financial Ratios, Financial Distress, Logistic Regression